2022
DOI: 10.2147/jpr.s376586
|View full text |Cite
|
Sign up to set email alerts
|

Pain Management in a Prehospital Emergency Setting: A Retrospective Observational Study

Abstract: Purpose Acute pain is a prevalent symptomatology in prehospital emergency care. Although inadequate assessment and treatment of acute pain are associated with various complications, about 43% of adults suffering from pain are undertreated. This phenomenon is poorly studied, and limited data are available in the literature. The objective was to investigate the pain management in a prehospital emergency health-care setting, verifying pain assessment, pharmacological treatment adherence and the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…An analysis of this would have strengthened conclusions on sex-specific disparities by O'Connor et al 37 Lourens et al 47 found an association with higher analgesic administration among higher qualified paramedics, which may be due to access to a wider range of medications. This was similar to Ferri et al 46 who found that statistically lower rates of analgesic administration were noted in nurse-staffed ambulances, as opposed to ambulances staffed by both a doctor and nurse acting in a paramedic capacity. These findings indicate the need to increase scope of practice through further inter-professional training and education, thorough investigation into how certain medications act differently in males and females, and how to incorporate sex-specificity in analgesic decision making.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…An analysis of this would have strengthened conclusions on sex-specific disparities by O'Connor et al 37 Lourens et al 47 found an association with higher analgesic administration among higher qualified paramedics, which may be due to access to a wider range of medications. This was similar to Ferri et al 46 who found that statistically lower rates of analgesic administration were noted in nurse-staffed ambulances, as opposed to ambulances staffed by both a doctor and nurse acting in a paramedic capacity. These findings indicate the need to increase scope of practice through further inter-professional training and education, thorough investigation into how certain medications act differently in males and females, and how to incorporate sex-specificity in analgesic decision making.…”
Section: Discussionsupporting
confidence: 88%
“…This understanding was further highlighted in the other included studies which indicated that analgesic administration was not influenced by the sex of the patient, even after controlling for potential confounders. 39,4548…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations